Examination Of Ecclesiastical Strategies for Implementing AI-Generated Content In Alignment with Philippians 4:8 - Hutagalung, Stimson (Fakultas Filsafat Universitas Advent Indonesia, 2025)
Fostering comprehensive spiritual growth was both facilitated and complicated by the rapid integration of digital technology and artificial intelligence (AI) in contemporary church ministry. Digitalization enhanced ministry effectiveness, involvement, and communication, yet research indicated that technological advancement did not necessarily foster spiritual maturity. Many churches used AI-generated sermons, devotionals, and media without a theological framework to ensure that such content strengthened faith rather than merely boosting visibility. Grounded in the moral and theological precepts of Philippians 4:8, this study sought to develop a strategic model for AI use in church ministry. It employed a qualitative literature-based method and synthesized empirical studies on digital churches, reports on AI-enabled ministry, and contemporary theological scholarship to evaluate how the chapter’s eight virtues could guide content filtering and digital governance. The results identified five pillars: mission-oriented design, theological oversight, discernment-based curation, ethical-aesthetic coherence, and spiritual impact assessment. Through Spirit-led digital stewardship, this study presented a biblical value-anchored AI paradigm that positioned AI as a servant of the Gospel.